Preparation and characterization of baru (Dipteryx alata Vog) nut protein isolate and comparison of its physico-chemical properties with commercial animal and plant protein isolates - Nunes, Ângela A.; Favaro, Simone P; Miranda, Cesar H B; Neves, Valdir A [UNESP] (Wiley, 2017)
BACKGROUND: The Brazilian leguminous tree locally known in the Cerrado Biome as baru (Dipteryx alata Vog), provides a healthy edible oil source. The proteinaceous cake remaining after oil extraction could be transformed into new products to foodstuff development, such as protein concentrates and isolates, adding value to the production chain. In this study, it is described the preparation and characterization of baru nut protein isolate (BPI) from deffated baru flour, and measurements of its functional, nutritional, and thermal properties, in comparison to the more common vegetable (soybeans) and animal (casein and albumin) protein sources of the food industry. RESULTS: BPI presented higher protein content than soybean, casein and albumin commercial protein isolates, despite losses of albumins and low molecular weight globulins during the isolation procedure. Thermodynamics studies suggested that BPI has a well-conserved protein arrangement and lower thermostability than the other protein sources. BPI showed high in vitro digestibility and suitable and desirable functional properties such as water and oil absorption capacity, emulsifying activity, and foam formation and stability at mild and neutral pH. CONCLUSION: BPI could be used either as a substitute ingredient in oily food formulations or in the development of new products of its own. © 2016 Society of Chemical Industry.
Keywords: Ditperyx alata; functional properties; protein isolate, in vitro digestibility; solubility; thermal analysis